Prácticas higiénicas y presencia de staphylococcus aureus y coliformes fecales en manipuladores de alimentos de una institución universitaria - Vásquez Valles, María Nelly (2014)
The objective of the present investigation was determinate the presence of Staphylococcus aureus and coliformes fecales on food handlers of the universitary institution. The samples were nasal, pharyngeal secretions, water of hand washing and food samples: chili pepper, salad, mayonnaise and mixed juice; the samples were made according the INS and ICMSF, isolating Staphylococcus aureus and faecal coliforms in foods and food handlers with a high significative relation with a 95 percent of reliability and a 63 percent of degree relationship between total bacteria found between food handlers and different foods of cafes with to establish the relationship within hygiene practice to meet the microorganisms on food handlers and its presence on the foods